2006
DOI: 10.1136/bjo.2006.102152
|View full text |Cite
|
Sign up to set email alerts
|

Autologous retinal pigment epithelium-choroid sheet transplantation in age related macular degeneration: morphological and functional results

Abstract: Objective: To evaluate the outcome of autologous retinal pigment epithelium (RPE)-choroid sheet transplantation after removal of a subfoveal choroidal neovascularisation (CNV) in patients with age related macular degeneration (AMD). Methods: RPE-choroid sheet transplantation was performed in 10 consecutive patients with exudative AMD (n = 9) or geographic atrophy (n = 1). After CNV extraction, an autologous RPE-choroid patch was translocated from the midperiphery under the macula. Follow-up was between 6 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 22 publications
2
39
0
3
Order By: Relevance
“…Using various techniques to study fixation, previous studies have also shown 40 to 74% of eyes achieved fixation over the graft. [34][35][36][37][38][39] Similar to that reported by Maaijwee et al, we also found that fixation stability may worsen or improve during follow-up. 40 The reason for worsening of fixation stability may be related to delayed cystic change or atrophy whereas improvement in stability may be related to adaptation to eccentric fixation and viewing.…”
Section: Discussionsupporting
confidence: 85%
“…Using various techniques to study fixation, previous studies have also shown 40 to 74% of eyes achieved fixation over the graft. [34][35][36][37][38][39] Similar to that reported by Maaijwee et al, we also found that fixation stability may worsen or improve during follow-up. 40 The reason for worsening of fixation stability may be related to delayed cystic change or atrophy whereas improvement in stability may be related to adaptation to eccentric fixation and viewing.…”
Section: Discussionsupporting
confidence: 85%
“…No such complications were observed in our study. Early and late postoperative complications in human subjects, however, have included intraocular hemorrhage, serous macular detachment, epiretinal membrane formation, the development of proliferative vitreoretinopathy, or the induction of choroidal neovascularization in a patient who previously had dAMD [23,25].…”
Section: Discussionmentioning
confidence: 99%
“…One of the techniques used in human patients has been removal of CNVs from the abnormally neovascularized Brush's membrane, followed by autologous transplantation of RPE cells subretinally to allow repopulation of the Bruch's membrane. 10,11 Although this technique is effective in removing the CNVs, an undesirable consequence is the stripping of RPE cells and removal of the basement membrane of Bruch's exposing the deeper collagenous layers. However, functional recovery post-RPE transplantation has been shown to be limited because most of the RPE cells die shortly after transplantation, and they do not migrate out from the site of implantation.…”
Section: Introductionmentioning
confidence: 99%